1969
DOI: 10.12669/pjms.321.8379
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of physical activity among persons with type 2 diabetes with special consideration to daily routine.

Abstract: Objective:Physical activity is essential in maintaining a healthy lifestyle. Physical activity can improve general health, quality of life and diabetes management. The aim and objective of the study was to assess the physical activity trends in daily routine of people with type 2 diabetes.Methods:Two hundred persons with diabetes from four different clinical settings were included to access the trends of physical activity using a customized questionnaire EPIC-2. Pattern of physical activity was assessed across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Walking is preferred by people from SA cultural backgrounds, whether residing in their native countries such as Pakistan [7,42] or in the West [18,28]; this is supported by the current study. Previous studies have reported reasons for not engaging in PA similar to some of the reasons noted here, including household routines; difficulty finding the time [19,27,43]; cultural limitations such as requirements for a same-gender environment, which is unavailable in gyms [28]; a lack of places to go for a walk [27,44]; and the absence of a family member to walk with [42].…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Walking is preferred by people from SA cultural backgrounds, whether residing in their native countries such as Pakistan [7,42] or in the West [18,28]; this is supported by the current study. Previous studies have reported reasons for not engaging in PA similar to some of the reasons noted here, including household routines; difficulty finding the time [19,27,43]; cultural limitations such as requirements for a same-gender environment, which is unavailable in gyms [28]; a lack of places to go for a walk [27,44]; and the absence of a family member to walk with [42].…”
Section: Discussionsupporting
confidence: 73%
“…The number of cases in Pakistan is expected to rise to 13.8 million in 2030, raising concerns and suggesting a need to explore diabetes management and control [6]. One reason for the increased prevalence of T2DM in SA countries, such as Pakistan, is a carbohydrate-rich diet and physical inactivity [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations